2005
DOI: 10.1177/0148607105029004298
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fasting: An Outdated Concept?

Abstract: Recent studies have shown that fasting during the preoperative period for elective surgery induces a metabolic state that seems unfavorable for patients. Results from animal studies indicate that rapid depletion of liver glycogen before surgery leads to mobilization of muscle glycogen after surgery, in turn leading to reduced muscle strength. Depletion of liver glycogen also influences the function of the mononuclear phagocytic system (MPS), which is located predominantly in the liver. The MPS is essential in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 42 publications
1
32
0
10
Order By: Relevance
“…In the setting of mechanical bowel preparation, preoperative fasting can be as long as 40 h [4]. Prolonged fasting is deleterious for the patient since the post-operative period is characterised by increased metabolic rate, hypercatabolism, gluconeogenesis and insulin resistance [5], a key determinant of post-operative outcome and an independent predictor of the length of hospital stay after surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of mechanical bowel preparation, preoperative fasting can be as long as 40 h [4]. Prolonged fasting is deleterious for the patient since the post-operative period is characterised by increased metabolic rate, hypercatabolism, gluconeogenesis and insulin resistance [5], a key determinant of post-operative outcome and an independent predictor of the length of hospital stay after surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors have used new strategies in perioperative care for patients, abandon ing bowel preparation, fluid overload, preoperative fast ing, premedication, nasogastric tubes and drains and favoring stimulation of gut motility and carbohydrate loading [24,25]. In animal studies, rodents that were fed before stress induction showed improved muscle and cardiac function, better immunologic performance and, most prominently, better survival rates with complete recovery after hemorrhage or endotoxemia when com pared with fasting subjects [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, processes such as gluconeogenesis, and fat and protein catabolism are heightened during the perioperative period (54). Surgery itself results in a physiological state of hypercatabolism which is further compounded by the metabolic stress of preoperative fasting.…”
Section: Elective Surgery and Fasting Guidelinesmentioning
confidence: 99%